INFLUENCE OF SOLID PARTICLE AND SOYBEAN OIL OF PICKERING EMULSION DICLOFENAC DIETHYLAMINE USING TAGUCHI METHOD - Hutami, Shabrina Nindya; Kuncahyo, Ilham; Sulaiman, TN Saifullah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Emulsions stabilized by solid particles are called Pickering emulsions, using diclofenac diethylamine for topical use. In this study, screening for the effect of the type of solid particles (bentonite 3%; Avicel RC-591 2.5%; and kaolin 15%) and soybean oil concentration (10%; 20%, and 30%) using the Taguchi orthogonal array method, with independent variables (type of solid particles and concentration of soybean oil, dependent variables (viscosity, pH, %EE, creaming index, globule size, and % cumulative penetration). The Pickering emulsion with Avicel RC-591 for solid particles produced a stable emulsion during 21 days of storage. Using the Taguchi orthogonal array method, the best formula based on the dependent variable is Formula 4 with physical test results at viscosity 566 cp, pH value 8.18, adsorption efficiency 55.70%, creaming index 100%, globule size 57.1 µm, cell diffusion Franz test at 120 minutes resulted in a cumulative penetration of 69.829%. The penetration power of Formula 4 is better than the emulsion with tween and span emulsifiers, which has a cumulative amount at 120 minutes of 12.609%. Therefore, Avicel RC-591 2.5% solid particles with 10% soybean oil concentration resulted in a stable Pickering emulsion and better penetration than emulsions with tween and span emulsifiers.